Laser treatment of congenital melanocytic nevi: a review of the literature. Issue 1 (January 2016) - Bray, Fleta; Shah, Vidhi; Nouri, Keyvan
Abstract Congenital melanocytic nevi (CMN) are nevi that are present from birth and occur in approximately 1 % of newborns. CMN may be cosmetically disfiguring and are at risk for malignant transformation. For these two reasons, CMN are frequently treated. A variety of treatment modalities have been utilized with variable efficacy, including excision, dermabrasion, curettage, chemical peels, radiation therapy, cryotherapy, electrosurgery, and lasers. The current treatment of choice for CMN is surgical excision. However, some CMN occur in cosmetically sensitive areas, where a surgical scar is less acceptable, or in inoperable locations. For these reasons, there has been increasing interest in the potential for laser treatment of CMN. The lasers that have been studied to date for the treatment of CMN include pigment-specific lasers, including ruby (694 nm), alexandrite (755 nm), and Nd:yttrium aluminum garnet (YAG) (1064 nm), as well as ablative laser treatment with CO2 laser (10, 600 nm) and Er:YAG (2940 nm). To date, ruby lasers have been studied most extensively in the treatment of CMN. Ruby laser has been shown to improve the cosmetic appearance of some CMN and may be cautiously considered for lesions located in cosmetically sensitive areas that are less amenable to surgical excision. For very large CMN, ruby laser has been tried as an alternative to extensive surgical and grafting procedures. Dual treatment with Q-switched ruby laser and normal mode ruby laser may provide the best outcomes; however, multiple treatment sessions should be anticipated. The practicality and expense of multiple treatments should be discussed with the patient prior to initiating treatment. Importantly, because of the persistence of dermal nevus cells, lifelong follow-up is required for all laser-treated CMN, even those with excellent cosmetic effect.